Draft Annual Plan 2011-12 Volume - I Government of Karnataka - Planning Commission (Planning Commission, 2011)
Karnataka has a rich heritage, inspiring its people to create a bright future. With its special geographical location full of variety-its rivers, hills, valleys, plains, forests and resources-the State is known for its tourist and industrial potential. Its long history of over 2,000 years has left many beautiful forts, tanks, temples, mosques and towns of historical importance to the posterity. These old towns have grown to be industrial, commercial and educational centres. They are provided with all modem facilities. Bordered by the Western Ghats with tall peaks and lush greenery in the west, the tableland is fertile because of its black soil and river and tank irrigation facilities. the coastal strip to the west of the Ghats is renowned for its silvery beaches and rich green paddy fields.
Government of Karnataka, Planning, Programme Monitoring and Statistics Department